(untitled) (Baghdad Science Journal, 2023)
Gastritis can be defined as histological inflammation of the gastric mucosa. It can be classified according to the time course of the disease as acute or chronic, histological findings, anatomic location, and pathological mechanisms. The objective of this study was to evaluation of serum levels of the proinflammatory cytokines IL-8, IL-17 and IL-22 in Helicobacter pylori infection and their association with the degree of gastritis histopathology in a sample of Iraqi patients. The case-control prospective study consists of 60 patients who attended the Gastrointestinal Tract Center at Al-Kindy Teaching Hospital during the period from December 2019 to April 2020. In addition, the control group included 60 apparently healthy individuals. Biopsies from the gastric antrum and/or body mucosa were used to assess the severity of chronic inflammation, neutrophil infiltration, atrophy, intestinal metaplasia. Serum samples were obtained to determine H. pylori infection, circulating interleukin (IL)-8, IL-17, and IL-22. Results showed that the Patients’ ages with gastritis ranged from 18-75 years. The body mass index revealed that 33.33% of the patients were obese and 35% of them were overweight. Most of the patients with active chronic gastritis and superficial chronic gastritis had positive titers for anti-H. pylori IgG antibody (167.89 ± 3.18 IU/ml) and (150.74± 1.45 IU/ml) respectively, which was significantly different from the control group (4.36 ± 0.29 IU/ml) (P=0.0001). Histopathological analysis showed that all subjects experienced chronic inflammation, while neutrophil infiltration was found 36.66% and there was significant association between serum levels of IL-8, IL-17, and IL-22 with a degree of chronic inflammation and neutrophils infiltration. In conclusion, the most common cause of gastritis was H. pylori with histopathological lesions, showing neutrophils infiltration and chronic gastric mucosal inflammation associated with increased levels of IL-8, IL-17, and IL-22 in serum.